THE PROBLEM OF GENDER BALANCE AND WOMEN’S VISI-BILITY IN MEDIA DURING THE WAR - Balalaieva, Olena (Revista Conhecimento Online: Diversidade e Inclusão Social, 2025)
Today, Ukraine has a unique experience of overcoming gender stereotypes at a new stage of building gender equality during the war, the study of which can be useful for the broader research community. Promoting gender equality during wartime is not only an ethical value but also a strategic necessity and studying gendered discourses and social practices is crucial. The study aims to analyse the gender balance and peculiarities of gender representation, stereotypes, and discrimination in war themes in Ukrainian online media content. The article focuses more on the problem of women's representation in media content. The paper provides the latest data from four independent monitoring studies of Ukrainian national and regional online media. Their results show that indirect rather than direct gender discrimination is characteristic of Ukrainian media, and the national media landscape is characterized by an indirect reflection of gender inequality already present in society: men dominate in the majority of thematic areas and topics, including war. Despite the fact that women are still underrepresented or misrepresented in media content positive changes in multidimensional representation and portrayal of women are fixed both by monitoring data and by analytical studies confirming the transformation of gender roles in Ukrainian society in wartime.